Further Semiotic Perspectives on the Outcome-Based vs Performance-Based Semantic Dispute - Korkeamäki, Lauri (Palgrave Macmillan, 2021)
The current book chapter addresses the result-oriented servitization business models coined in the academic literature as outcome-based contracts or performance-based contracts. Indeed, the given polarization in terms of academic terminology certainly does not serve to decrease the conceptual complexity of these business models. As extant arguments with the pro “outcome” prefix have built on its unambiguousness compared to “performance,” I intend to provide further insights into the debate by offering pragmatics- and syntax-based perspectives on the topic. In this effort, I draw upon a systematic literature review of over 80 top-tier academic journal papers (AJG3, AJG4, and AJG4*). Thus, the current chapter contributes to the concept stream of the outcome-based service (OBS) literature. For managers, the chapter synthesizes research trends, offers an outlook of the eminent research facets that publish on the topic, and provides some contextualized explanations and antecedents of the differences in academic terminology.
Keywords: Outcome-based contracts; Performance-based contracts; Servitization; fi=Strateginen johtaminen|en=Strategic Management|